VIABILITAS SEMEN SAPI SIMENTAL YANG DIBEKUKAN MENGGUNAKAN KRIOPROTEKTAN GLISEROL - Muhamad Ilyas Mumu (Universitas Tadulako, 2009)
This experiment used semen from a Simental bull, age 4 years old, 850 kg in weight and was healthy especially his reproduction organ. Semen collection was done twice a week using an artificial vagina. Soon after the semen was evaluated, it was diluted with tris aminomethan plus egg yolk and three concentration of glycerol namely 3% (G1), 5% (G2) and 7% (G3). The semen was packed in 0.25 ml straw and maintained in equilibrium at 5oC for 4 hours and frozen in liquid nitrogen for 60 minutes. Data collected were motility and percentage of living spermatozoa after freezing. The experiment used a Completely Randomized Block Design. The results showed that motility and percentage of living spermatozoa after freezing for each treatment were not significant (P>0.05). The effect of those three treatments on motility and percentage of living spermatozoa after freezing were 40.2% and 59.6% for G1, 41.2% and 63.8% for G2 and 39.8% and 57.8% for G3, respectively, but the G2 treatment was better in protecting the quality of the spermatozoa than the other treatments. It was appeared that the level of glycerol at 5% concentration is an optimal dosage for maintaining the quality of the frozen semen